Paeonol Ameliorates Chronic Itch and Spinal Astrocytic Activation via CXCR3 in an Experimental Dry Skin Model in Mice - Wang, Wen; Li, Qiaoyun; Zhao, Zhongqiu; Liu, Yutong; Wang, Yi; Xiong, Hui; Mei, Zhinan (Frontiers in Pharmacology, 2022)
Paeonol is a bioactive phenol presents mainly in Paeonia suffruticosa Andr. (Paeoniaceae), Paeonia lactiflora Pall., and Dioscorea japonica Thunb. (Dioscoreaceae), harboring various pharmacological activities including anti-inflammatory, antioxidant, immune regulatory and reverse chemoresistance activity. Recent reports revealed paeonol exhibited good effects on chronic dermatitis, such as atopic dermatitis (AD) and psoriasis. However, whether paeonol is effective for dry skin disease and its mechanism of action still remain unclear. In this study, we analysed the effects of paeonol on a mouse model of dry skin treated with acetone-ether-water (AEW), which showed impressive activities in reducing scratching behaviour and skin inflammation. To elucidate the underlying molecular targets for the anti-pruritic ability of paeonol, we screened the expression of possible chemokine pathways in the spinal cord. The expression of CXCR3 was significantly alleviated by paeonol, which increased greatly in the spinal neurons of AEW mice. In addition, treatment of paeonol significantly inhibited AEW-induced expression of astrocyte activity-dependent genes including Tlr4, Lcn2 and Hspb1 et al. The inhibitory effects of paeonol on scratching behavior and astrocytic activation in the spinal cord induced by AEW were abolished when CXCR3 was antagonized or genetically ablated. Taken together, our results indicated that paeonol can ameliorate AEW-induced inflammatory response and itching behavior, and reduce the expression of spinal astrocyte activity-dependent genes induced by AEW, which are driven by CXCR3.